2021
DOI: 10.1111/btp.12939
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution mapping identifies habitat characteristics of the invasive vine Antigonon leptopus on St. Eustatius (Lesser Antilles)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Furthermore, this limited number of countries constrained the number of studied IAP using RS platforms providing a partial picture of the invasions on a global scale. A large number of IAP impinging coastal ecosystems worldwide are still needed of specific RS research and applications [52,90,91], albeit the research in this field is progressing as shown by promising results in 2022 [92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this limited number of countries constrained the number of studied IAP using RS platforms providing a partial picture of the invasions on a global scale. A large number of IAP impinging coastal ecosystems worldwide are still needed of specific RS research and applications [52,90,91], albeit the research in this field is progressing as shown by promising results in 2022 [92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…However, as habitat occurrence and quality are continuously being reduced in the Anthropocene, equally are local species abundances (Dirzo et al, 2014; Otto, 2018), with habitat loss alone predicted to drive the extinction of nearly 2,000 terrestrial vertebrate species (Powers & Jetz, 2019). On St. Eustatius, over 30% of the island's surface is directly and heavily affected by human presence (Figure 2), with most habitats additionally being degraded by a large feral goat population, as well as the presence of nonnative and invasive plant species (van Andel et al, 2016; Haber et al, 2021). While the latest assessments estimated an iguana population size of 300–600 individuals (Debrot et al, 2013; Fogarty et al, 2004), considering population densities on islands uninhabited by humans (Angin, 2017), as well as abundances in high‐quality, small less‐disturbed areas on St. Eustatius (Debrot et al, 2013; present study), the pre‐colonization population size was arguably several magnitudes larger.…”
Section: Discussionmentioning
confidence: 99%
“…Semantic segmentation can represent the process of assigning a semantic label to each coherent region of an image. This coherent region is represented by a pixel [31], a subpixel [32], a super-pixel [33] or an image patch composed of several pixels [34].…”
Section: Introductionmentioning
confidence: 99%